Solvent-resistant HIPS composite material, preparation method thereof and product thereof

CN121379011BActive Publication Date: 2026-10-20KINGFA SCI & TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511688018.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-18
Publication Date
2026-10-20
Estimated Expiration
2045-11-18

AI Technical Summary

Technical Problem

例如,将HIPS树脂用于制作冰箱内衬(内胆),但由于冰箱内衬需要与各种发泡剂(环戊烷发泡剂以及含碳氟化合物类发泡剂)以及动植物油接触,导致以常规挤出级HIPS树脂制成的冰箱内胆易出现龟裂或暗裂;而且,冰箱冷冻室的使用温度通常在0℃以下,使得冰箱内衬在使用过程常受到周期性的应力冲击,从而导致其易发生开裂

Benefits of technology

本发明以特定重均分子量和熔体质量流动速率的HIPS树脂与硫化剂相结合,利用硫化剂在熔融加工过程中引发HIPS树脂中的聚苯乙烯相的分子链间交联形成三维网络结构,高分子量的HIPS树脂能够提供更多可交联位点以提高交联网络的交联点密度,而兼具低熔体质量流动速率的HIPS树脂能够提供大量的支链结构,使得所形成的交联网络可以物理阻隔溶剂分子的渗透;同时,大粒径的蒙脱土I和小粒径的蒙脱土II相结合可交织在一起形成曲折且复杂的渗透路径,相当于在HIPS树脂中构建阻止溶剂渗透的物理屏障;而且,蒙脱土还能利用其与HIPS分子链之间的相互作用以限制HIPS分子链的运动能力,使得溶剂分子难以侵入HIPS树脂中,进而有效抑制溶剂分子的渗透;而硫化剂还可作用于HIPS树脂中的聚丁二烯橡胶相,使其形成化学交联点以减少界面缺陷,来抑制溶剂沿界面扩散,进而提高HIPS复合材料的耐溶剂性能。此外,上述交联网络中的交联点可以作为锚定点,迫使裂纹扩展路径迂曲化,并通过银纹-剪切带机制吸收冲击能量,以及利用交联网络来均匀化应力,进而提高HIPS复合材料的低温抗开裂性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to a kind of solvent-resistant HIPS composite material and its preparation method, preparation, belong to the technical field of polymer compound composition.The solvent-resistant HIPS composite material of the present application includes HIPS resin, montmorillonite and vulcanizing agent;The weight average molecular weight of the HIPS resin is 40000g / mol;The melt mass flow rate of the HIPS resin under the condition of 200 DEG C, 5kg is less than or equal to 5g / 10min;The montmorillonite includes montmorillonite I and montmorillonite II, the particle size D50 of the montmorillonite I is 30 μm to 40 μm, the particle size D50 of the montmorillonite II is 5 μm to 10 μm;The mass fraction of the montmorillonite relative to HIPS resin is 2% to 10%;The mass fraction of the vulcanizing agent relative to HIPS resin is 0.01% to 0.5%.The solvent-resistant HIPS composite material has good solvent resistance and excellent low-temperature crack resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer compound composition technology, and more particularly to a solvent-resistant HIPS composite material and its preparation method and components. Background Technology

[0002] HIPS (High Impact Polystyrene) is a thermoplastic resin modified by introducing rubber components into polystyrene (PS). Due to its excellent impact resistance, high rigidity, low-temperature resistance, and electrical properties, it is widely used in electronics, instruments, and daily necessities. For example, HIPS resin is used to make refrigerator liners (inner liners). However, because refrigerator liners need to come into contact with various foaming agents (cyclopentane foaming agents and fluorocarbon-containing foaming agents) and animal and vegetable oils, refrigerator liners made from conventional extrusion-grade HIPS resin are prone to cracking or micro-cracks. Furthermore, the operating temperature of the refrigerator freezer compartment is usually below 0°C, causing the refrigerator liner to be subjected to periodic stress impacts during use, making it susceptible to cracking. Summary of the Invention

[0003] The purpose of this invention is to overcome the shortcomings of the prior art and provide a solvent-resistant HIPS composite material, its preparation method, and the parts thereof.

[0004] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a solvent-resistant HIPS composite material comprising HIPS resin, montmorillonite, and a vulcanizing agent; The weight-average molecular weight (Mw) of the HIPS resin is ≥40000 g / mol (Mw can be determined by gel permeation chromatography). The HIPS resin has a melt flow rate of ≤5 g / 10 min at 200℃ and 5 kg (test standard is ISO 1133-1:2022); The montmorillonite includes montmorillonite I and montmorillonite II, wherein the particle size D50 of montmorillonite I is 30 μm to 40 μm, and the particle size D50 of montmorillonite II is 5 μm to 10 μm. The mass fraction of montmorillonite relative to HIPS resin is 2% to 10%; The vulcanizing agent has a mass fraction of 0.01% to 0.5% relative to the HIPS resin.

[0005] This invention combines HIPS resin with specific weight-average molecular weight and melt flow rate with a vulcanizing agent. During melt processing, the vulcanizing agent initiates cross-linking between the polystyrene (PS) phase molecular chains in the HIPS resin, forming a three-dimensional network structure. The high molecular weight of the HIPS resin provides more cross-linkable sites, increasing the cross-link density of the network, while the low melt flow rate provides numerous branched structures, allowing the resulting cross-link network to physically block solvent molecule penetration. Simultaneously, large-particle montmorillonite I and small-particle montmorillonite II intertwine to form a tortuous and complex penetration path, effectively creating a physical barrier against solvent penetration within the HIPS resin. Furthermore, montmorillonite interacts with the HIPS molecular chains to restrict their movement, making it difficult for solvent molecules to penetrate the resin and thus effectively inhibiting solvent penetration. The vulcanizing agent also acts on the polybutadiene (PB) rubber phase in the HIPS resin, forming chemical cross-linking points to reduce interfacial defects and inhibit solvent diffusion along the interface, thereby improving the solvent resistance of the HIPS composite material. Furthermore, the crosslinking points in the aforementioned crosslinking network can serve as anchoring points, forcing the crack propagation path to become tortuous, absorbing impact energy through the crazing-shear band mechanism, and using the crosslinking network to homogenize stress, thereby improving the low-temperature crack resistance of HIPS composite materials.

[0006] The HIPS resin in the solvent-resistant HIPS composite material of the present invention is the matrix resin, and its mass percentage content in the solvent-resistant HIPS composite material is ≥90%.

[0007] The particle size D50 of montmorillonite can be determined with reference to GB / T 19077.1-2008 "Particle size analysis by laser diffraction".

[0008] In some embodiments, the particle size D50 of the montmorillonite I may be, but is not limited to, a range of any or both of 30 μm, 31 μm, 32 μm, 33 μm, 34 μm, 35 μm, 36 μm, 37 μm, 38 μm, 39 μm, and 40 μm.

[0009] In some embodiments, the particle size D50 of the montmorillonite II may be, but is not limited to, a range of any one or both of 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, and 10 μm.

[0010] In some embodiments, the mass fraction of montmorillonite relative to HIPS resin may be, but is not limited to, any or both of the following values: 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.

[0011] In some embodiments, the mass fraction of the vulcanizing agent relative to the HIPS resin may be, but is not limited to, a range of any one or both of 0.01%, 0.03%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, and 0.5%.

[0012] In some embodiments, the mass ratio of montmorillonite I to montmorillonite II is from 0.5:1 to 2:1, for example, but not limited to any one or both of the following: 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, and 2:1.

[0013] In some embodiments, the montmorillonite is inorganic montmorillonite and / or organic montmorillonite.

[0014] Inorganic montmorillonite refers to sodium-based / calcium-based montmorillonite obtained directly from mining and then drying, crushing, and screening, or montmorillonite modified through heat treatment, acid activation, inorganic salt pillaring, etc.

[0015] Organo-montmorillonite refers to montmorillonite in which organic modifiers (cationic surfactants, polymers, silanes, etc.) are introduced between natural montmorillonite layers through ion exchange, covalent bonds, hydrogen bonds, etc.; for example, the organic modifier can be a quaternary ammonium salt organic treatment agent, wherein the quaternary ammonium salt is preferably a long-chain alkyl quaternary ammonium salt.

[0016] In some embodiments, the long-chain alkyl quaternary ammonium salt includes, but is not limited to, HOOC(CH2). 17 NH3 + CH3(CH2) 17 N(CH3)[(CH2CH2OH)2] + [CH3(CH2)] 17 ]2N(CH3)2 + CH3(CH2) 17 NH3 + CH3(CH2) 16 CH2NH2, CH3(CH2) 17 N(CH3)3 + At least one of them.

[0017] As a preferred embodiment of the solvent-resistant HIPS composite material of the present invention, the weight-average molecular weight of the HIPS resin is from 44,000 g / mol to 176,000 g / mol, for example, but not limited to any one or any two of the following values: 44,000 g / mol, 50,000 g / mol, 60,000 g / mol, 80,000 g / mol, 100,000 g / mol, 120,000 g / mol, 140,000 g / mol, 160,000 g / mol, and 176,000 g / mol.

[0018] As a preferred embodiment of the solvent-resistant HIPS composite material of the present invention, the molecular weight distribution coefficient (PDI) of the HIPS resin is 2 to 4, for example, but not limited to any one or any two of 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4.

[0019] Studies have found that when the molecular weight distribution coefficient of HIPS resin is between 2 and 4, it is possible to better utilize long-chain molecules to induce crazes and short-chain molecules to promote shear yielding, thereby enhancing energy dissipation. It is also conducive to balancing the network density of the crosslinked network and the activity of molecular chains, thus better improving the solvent resistance and low-temperature crack resistance of HIPS composite materials.

[0020] As a preferred embodiment of the solvent-resistant HIPS composite material of the present invention, the melt mass flow rate of the HIPS resin at 200°C and 5 kg is 3 g / 10 min to 4.8 g / 10 min, for example, but not limited to any one or any two of the following values: 3 g / 10 min, 3.2 g / 10 min, 3.4 g / 10 min, 3.6 g / 10 min, 3.8 g / 10 min, 4 g / 10 min, 4.2 g / 10 min, 4.4 g / 10 min, 4.6 g / 10 min, and 4.8 g / 10 min.

[0021] As a preferred embodiment of the solvent-resistant HIPS composite material of the present invention, the content of polybutadiene (PB) rubber phase in the HIPS resin is 6wt% to 12wt%, preferably 7wt% to 9wt%, for example, but not limited to any one or any two of 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, and 12wt%.

[0022] The mass content of polybutadiene (PB) rubber phase in HIPS resin can be determined by thermogravimetric analysis (TGA), as follows: Take 5 mg to 10 mg of sample and heat it from 20 °C to 800 °C at a heating rate of 10 °C / min in air. In air, due to its unsaturated double bonds, the PB rubber phase undergoes oxidative degradation and combustion at a lower temperature (approximately 300 °C to 450 °C), exhibiting the first weight loss step. The polystyrene matrix is ​​relatively stable and decomposes at a higher temperature (approximately 400 °C to 500 °C), exhibiting the second weight loss step. By analyzing these two weight loss steps on the TGA curve, the PB rubber phase content in the HIPS resin can be obtained.

[0023] In a preferred embodiment of the solvent-resistant HIPS composite material of the present invention, the vulcanizing agent is an organic peroxide, which may include, but is not limited to, at least one of benzoyl peroxide (BPO), dicumyl peroxide (DCP), and di-tert-butyl peroxide (DTBP), preferably dicumyl peroxide.

[0024] As a preferred embodiment of the solvent-resistant HIPS composite material of the present invention, the solvent-resistant HIPS composite material further includes an antioxidant, wherein the antioxidant has a mass fraction of 0.1% to 0.3% relative to the HIPS resin.

[0025] Optionally, the antioxidant includes at least one of hindered phenolic antioxidants, phosphite antioxidants, metal alkyl thiophosphate antioxidants, carbamic acid antioxidants, and organosulfur antioxidants, preferably phosphate ester antioxidants.

[0026] Secondly, the present invention provides a method for preparing the above-mentioned solvent-resistant HIPS composite material, comprising the following steps: mixing the components evenly and then melting and extruding to obtain the solvent-resistant HIPS composite material.

[0027] Specifically, after the components are mixed, they pass through four temperature zones sequentially within the twin-screw extruder: First temperature zone: temperature is 180℃ to 220℃, residence time is 9.5s to 10.5s; Second temperature zone: temperature is 220℃ to 240℃, residence time is 14.5s to 14.5s; Third temperature zone: temperature is 220℃ to 250℃, residence time is 19.5s to 20.5s; Fourth temperature zone: temperature is 220℃ to 240℃, residence time is 9.5s to 10.5s.

[0028] Thirdly, the present invention provides a component made of the aforementioned solvent-resistant HIPS composite material.

[0029] In a preferred embodiment of the component described in this invention, the component is a refrigerator liner.

[0030] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention combines HIPS resin with specific weight-average molecular weight and melt flow rate with a vulcanizing agent. The vulcanizing agent initiates cross-linking between the polystyrene phase molecular chains in the HIPS resin during melt processing, forming a three-dimensional network structure. The high molecular weight of the HIPS resin provides more cross-linkable sites, increasing the cross-linking point density of the network, while the low melt flow rate provides numerous branched structures. This allows the formed cross-linked network to physically block solvent molecule penetration. Simultaneously, the combination of large-particle montmorillonite I and small-particle montmorillonite II interweaves to form a tortuous and complex penetration path, effectively constructing a physical barrier against solvent penetration within the HIPS resin. Furthermore, montmorillonite's interaction with the HIPS molecular chains restricts their mobility, making it difficult for solvent molecules to penetrate the HIPS resin, thus effectively inhibiting solvent penetration. The vulcanizing agent also acts on the polybutadiene rubber phase in the HIPS resin, forming chemical cross-linking points to reduce interfacial defects and inhibit solvent diffusion along the interface, thereby improving the solvent resistance of the HIPS composite material. Furthermore, the crosslinking points in the aforementioned crosslinking network can serve as anchoring points, forcing the crack propagation path to become tortuous, absorbing impact energy through the crazing-shear band mechanism, and using the crosslinking network to homogenize stress, thereby improving the low-temperature crack resistance of HIPS composite materials. Detailed Implementation

[0031] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0032] Unless otherwise specified, all other materials, reagents, etc. used in the examples and comparative examples are commercially available.

[0033] 1. Raw materials and reagents 1) HIPS resin 1 HIPS Resin 1: HIPS 8265, purchased from INEOS Styrol (Foshan) Co., Ltd.; its weight-average molecular weight (Mw) is 156,600 g / mol, molecular weight distribution index (PDI) is 2.97, melt flow rate (200℃, 5 kg) is 4.02 g / 10 min, and polybutadiene rubber phase content is 8 wt%. HIPS Resin 2: HIPS 350K, purchased from Guoheng Chemical Co., Ltd.; its weight-average molecular weight (Mw) is 44100 g / mol, molecular weight distribution coefficient (PDI) is 2.36, melt flow rate (200℃, 5 kg) is 4.64 g / 10 min, and polybutadiene rubber phase content is 8 wt%. HIPS resin 3: PS HI425TV NL, purchased from KUMHO PETROCHEMICAL CO.; its weight-average molecular weight (Mw) is 124700 g / mol, molecular weight distribution index (PDI) is 3.39, melt flow rate (200℃, 5 kg) is 12.44 g / 10 min, and polybutadiene rubber phase content is 8 wt%. HIPS resin 4: self-made; its weight-average molecular weight (Mw) is 13600 g / mol, its molecular weight distribution index (PDI) is 1.79, its melt flow rate (200℃, 5 kg) is 8.76 g / 10 min, and its polybutadiene rubber phase content is 8 wt%. The preparation method of HIPS resin 4 includes the following steps: S1. Raw material pretreatment: Dissolve cis-butadiene rubber in styrene solution, and then add initiator BPO to the styrene-rubber solution; the mass ratio of cis-butadiene rubber to styrene is 8:92. S2, Prepolymerization reaction: The mixture is placed in a polymerization reactor with a stirrer and polymerized at 85±5℃ for 0.5h; S3, Main polymerization reaction: The prepolymer is transferred to a tower reactor, and the temperature is gradually increased to 165±5℃ for polymerization reaction for 1.5h; S4. Deashing and granulation treatment.

[0034] HIPS resin 5: self-made; its weight-average molecular weight (Mw) is 175,300 g / mol, molecular weight distribution coefficient (PDI) is 3.65, melt flow rate (200℃, 5 kg) is 3.68 g / 10 min, and polybutadiene rubber phase content is 8 wt%. The preparation method of HIPS resin 5 includes the following steps: S1. Raw material pretreatment: Dissolve cis-butadiene rubber in styrene solution, and then add initiator BPO to the styrene-rubber solution; the mass ratio of cis-butadiene rubber to styrene is 8:92. S2, Prepolymerization reaction: The mixture is placed in a polymerization reactor with a stirrer and polymerized at 85±5℃ for 0.5h; S3, Main polymerization reaction: The prepolymer is transferred to a tower reactor and the temperature is gradually increased to 145±5℃ for polymerization reaction for 1 hour; S4. Deashing and granulation treatment.

[0035] HIPS resin 6: self-made; its weight-average molecular weight (Mw) is 115,500 g / mol, its molecular weight distribution index (PDI) is 2.48, its melt flow rate (200℃, 5 kg) is 4.84 g / 10 min, and its polybutadiene rubber phase content is 6 wt%. The preparation method of HIPS resin 6 includes the following steps: S1. Raw material pretreatment: Dissolve cis-butadiene rubber in styrene solution, and then add initiator BPO to the styrene-rubber solution; the mass ratio of cis-butadiene rubber to styrene is 6:94. S2, Prepolymerization reaction: The mixture is placed in a polymerization reactor with a stirrer and polymerized at 85±5℃ for 0.5h; S3, Main polymerization reaction: The prepolymer is transferred to a tower reactor and the temperature is gradually increased to 155±5℃ for polymerization reaction for 1 hour; S4. Deashing and granulation treatment.

[0036] HIPS resin 7: self-made; its weight-average molecular weight (Mw) is 132,200 g / mol, its molecular weight distribution coefficient (PDI) is 3.12, its melt flow rate (200℃, 5 kg) is 2.39 g / 10 min, and its polybutadiene rubber phase content is 12 wt%. The preparation method of HIPS resin 7 includes the following steps: S1. Raw material pretreatment: Dissolve cis-butadiene rubber in styrene solution, and then add initiator BPO to the styrene-rubber solution; the mass ratio of cis-butadiene rubber to styrene is 12:88. S2, Prepolymerization reaction: The mixture is placed in a polymerization reactor with a stirrer and polymerized at 85±5℃ for 0.5h; S3, Main polymerization reaction: The prepolymer is transferred to a tower reactor and the temperature is gradually increased to 155±5℃ for polymerization reaction for 1 hour; S4. Deashing and granulation treatment.

[0037] The weight-average molecular weight (Mw) and number-average molecular weight (Mn) of HIPS resins 1 to 7 were determined by gel permeation chromatography (GPC) with tetrahydrofuran (THF) as the solvent and polystyrene (PS) as the standard for calibration; the molecular weight distribution coefficient (PDI) = Mw / Mn.

[0038] 2) Montmorillonite Montmorillonite I-1, particle size D50=40μm; Montmorillonite I-2, particle size D50=30μm; Montmorillonite II-1, particle size D50=10μm; Montmorillonite II-2, particle size D50=5μm; The grade of montmorillonite I-1 mentioned above is DK2, manufactured by Zhejiang Fenghong New Material Co., Ltd.; montmorillonite I-2, montmorillonite II-1 and montmorillonite II-2 are all obtained by grinding and sieving montmorillonite I-1.

[0039] 3) Vulcanizing agent Vulcanizing agent 1 is dicumyl peroxide, which is commercially available; Vulcanizing agent 2 is benzoyl peroxide, which is commercially available; Vulcanizing agent 3 is di-tert-butyl peroxide, which is commercially available.

[0040] 4) Antioxidant, SONOX 621J, purchased from Shandong Linyi Sanfeng Chemical Co., Ltd.

[0041] 2. Preparation method of solvent-resistant HIPS composite material of the present invention According to the formula, the components are mixed evenly and then melt-extruded in a twin-screw extruder to obtain the solvent-resistant HIPS composite material; wherein, the material passes through four temperature zones sequentially within the twin-screw extruder: First temperature zone: temperature is 180℃ to 220℃, residence time is 9.5s to 10.5s; Second temperature zone: temperature is 220℃ to 240℃, residence time is 14.5s to 14.5s; Third temperature zone: temperature is 220℃ to 250℃, residence time is 19.5s to 20.5s; Fourth temperature zone: temperature is 220℃ to 240℃, residence time is 9.5s to 10.5s.

[0042] Table 1 shows the weight parts of each component in the solvent-resistant HIPS composite materials of Examples 1 to 9 and Comparative Examples 1 to 3. Table 2 shows the weight parts of each component in the solvent-resistant HIPS composite materials of Examples 10 to 13 and Comparative Examples 4 to 5. 3. Performance Testing 1) Solvent resistance test: Tensile specimens of solvent-resistant HIPS composite material were made and randomly divided into two groups, A and B. Group A: Tensile test was performed according to ISO 527 standard (specimen type 1A, tensile rate 50 mm / min) to obtain the tensile strength m; Group B: The tensile specimens were immersed in an acetone solution containing 0.1 wt% cyclopentane for 24 hours, then removed and dried. Tensile tests were performed according to ISO 527 standard (specimen type 1A, tensile rate 50 mm / min) to obtain the tensile strength n. Tensile strength retention rate (%) = n / m × 100%.

[0043] 2) Low-temperature crack resistance: Solvent-resistant HIPS composite material was made into sheet samples with a thickness of 3 mm and frozen at -30℃ for 8 hours; then a steel ball weighing 0.5 kg was placed at a certain height and allowed to fall freely to impact the frozen sheet sample. The low-temperature crack resistance was evaluated by the height at which the sheet sample just broke through the ball.

[0044] Table 3. Performance of solvent-resistant HIPS composite materials in each example and comparative example. According to the data in Table 3, the tensile strength retention rate of the solvent-resistant HIPS composite materials in Examples 1 to 13 after soaking in acetone solution of cyclopentane for 24 hours is ≥89%, and the drop height of the ball after freezing at -30℃ for 8 hours is ≥100cm. This indicates that the HIPS composite material of the present invention has both good solvent resistance and excellent low-temperature crack resistance.

[0045] Meanwhile, according to Example 1 and Comparative Example 1, it can be seen that the vulcanizing agent plays a key role in improving the solvent resistance and low-temperature crack resistance of HIPS composite materials. According to Comparative Examples 2 and 3, it can also be found that when the weight-average molecular weight of HIPS resin is ≥40000 g / mol and the melt mass flow rate is ≤5 g / 10 min, it is necessary to combine it with the vulcanizing agent to effectively improve the solvent resistance and low-temperature crack resistance of HIPS composite materials. According to Comparative Examples 4 and 5, it can be seen that using montmorillonite I or montmorillonite II alone is not effective in improving the solvent resistance and low-temperature crack resistance of HIPS composite materials.

[0046] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A solvent-resistant HIPS composite material, characterized in that, Includes HIPS resin, montmorillonite, and vulcanizing agents; The weight-average molecular weight of the HIPS resin is ≥40000 g / mol; The HIPS resin has a melt flow rate of ≤5g / 10min at 200℃ and 5kg. The montmorillonite includes montmorillonite I and montmorillonite II, wherein the particle size D50 of montmorillonite I is 30 μm to 40 μm, and the particle size D50 of montmorillonite II is 5 μm to 10 μm. The mass fraction of montmorillonite relative to HIPS resin is 2% to 10%; The vulcanizing agent has a mass fraction of 0.01% to 0.5% relative to the HIPS resin; The molecular weight distribution coefficient of the HIPS resin is 2 to 4; The HIPS resin contains 6 wt% to 12 wt% polybutadiene rubber phase.

2. The solvent-resistant HIPS composite material as described in claim 1, characterized in that, The weight-average molecular weight of the HIPS resin is from 44,000 g / mol to 176,000 g / mol.

3. The solvent-resistant HIPS composite material as described in claim 1, characterized in that, The HIPS resin has a melt flow rate of 3 g / 10 min to 4.8 g / 10 min at 200 °C and 5 kg.

4. The solvent-resistant HIPS composite material as described in claim 1, characterized in that, The vulcanizing agent is an organic peroxide, which includes at least one of benzoyl peroxide, dicumyl peroxide, and di-tert-butyl peroxide.

5. The solvent-resistant HIPS composite material as described in claim 1, characterized in that, The solvent-resistant HIPS composite material also includes an antioxidant, wherein the antioxidant has a mass fraction of 0.1% to 0.3% relative to the HIPS resin.

6. The method for preparing the solvent-resistant HIPS composite material according to any one of claims 1 to 5, characterized in that, The process includes the following steps: mixing the components evenly and then melting and extruding them to obtain a solvent-resistant HIPS composite material.

7. A component, characterized in that, Made from the solvent-resistant HIPS composite material according to any one of claims 1 to 5.

8. The part as described in claim 7, characterized in that, The component in question is a refrigerator liner.

Citation Information

Patent Citations

  • Thermoplastic Resin Compositions with Good ChemicalResistance and Flow-ability for a Refrigerator

    KR1020020052422A

  • Method of preparing rubber modified polystyrene resin composition with high gloss and impact resistance

    US20040254284A1